2005
DOI: 10.1086/432495
|View full text |Cite
|
Sign up to set email alerts
|

Variations in the Peak Position of the 6.2 μm Interstellar Emission Feature: A Tracer of N in the Interstellar Polycyclic Aromatic Hydrocarbon Population

Abstract: This paper presents the results of an investigation of the molecular characteristics that underlie the observed peak position and profile of the nominal 6.2 m interstellar emission band generally attributed to the CC stretching vibrations of polycyclic aromatic hydrocarbons (PAHs). It begins with a summary of recent experimental and theoretical studies of the spectroscopic properties of large (>30 carbon atoms) PAH cations as they relate to this aspect of the astrophysical problem. It then continues with an ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
311
2
11

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 294 publications
(334 citation statements)
references
References 69 publications
10
311
2
11
Order By: Relevance
“…Acridine and anthracene have previously been observed to be practically indistinguishable at ambient conditions using infrared spectroscopy (Fialkovskaya & Nefedov 1968;Langhoff et al 1998;Hudgins et al 2005). Vibrational assignments have been made for both molecules and are summarized in Table 2 (Brigodiot & Lebas 1972).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Acridine and anthracene have previously been observed to be practically indistinguishable at ambient conditions using infrared spectroscopy (Fialkovskaya & Nefedov 1968;Langhoff et al 1998;Hudgins et al 2005). Vibrational assignments have been made for both molecules and are summarized in Table 2 (Brigodiot & Lebas 1972).…”
Section: Resultsmentioning
confidence: 99%
“…The shift of the 6.2 μm peak to lower wavelengths is hypothesized to reflect N-substitution inside the PAH structure as opposed to on the outside edge. Multiple N-substitutions are predicted to have a similar peak-broadening effect (Langhoff et al 1998;Hudgins et al 2005). Although the consquences of varying levels of N-substitution have been studied, the effects of pressure on PANHs have not previously been investigated.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent applications include the study of nitrogen containing PAHs (Mattioda et al 2003), which have been suggested to provide a better match for the interstellar 6.2 µm emission band (Hudgins et al 2005;Peeters et al 2002), and of complexes of PAHs and atomic Fe, which have been suggested to be stable in interstellar clouds (Klotz et al 1996;Wang et al 2007). The method has also been applied to record PAH spectra in the far-infrared range of the spectrum (Mattioda et al 2009), where very molecule-specific vibrational modes -the socalled "drumhead" modes -are located.…”
Section: Matrix Isolation Spectroscopymentioning
confidence: 99%
“…18,22 Furthermore, CN provides a mechanism for incorporating nitrogen into the ring structure of polycyclic aromatic hydrocarbons to form polycyclic aromatic nitrogen heterocycles (PANHs). 23 Much improved fits to a 6.2 µm interstellar emission feature can be achieved by considering PANHs, 24 thus these species may provide a route to understanding the origins of the diffuse interstellar bands. 25 The need for additional spectroscopic studies of excited species relevant to astrochemistry has also recently been noted.…”
Section: Introductionmentioning
confidence: 99%